The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/smll.202301730
|View full text |Cite
|
Sign up to set email alerts
|

Nanosome‐Mediated Delivery Of Hdac Inhibitors and Oxygen Molecules for the Transcriptional Reactivation of Latent Hiv‐Infected Cd4+ T Cells

Abstract: The treatment of human immunodeficiency virus (HIV) infection is notoriously difficult due to the ability of this virus to remain latent in the host's CD4+ T cells. Histone deacetylases (HDACs) interfere with DNA transcription in HIV‐infected hosts, resulting in viral latency. Therefore, HDAC inhibitors can be used to activate viral transcription in latently infected cells, after which the virus can be eliminated through a shock‐and‐kill strategy. Here, a drug delivery system is developed to effectively delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…A novel drug delivery system utilizing oxygen-containing nanosomes has been developed to efficiently transport HDAC inhibitors to dormant HIV-infected cells. Incorporating oxygen nanosomes in this study alleviates drug toxicity and regulates the rate of drug release ( 180 ). The administration of BET inhibitors also presents side effects.…”
Section: Discussion and Expectationsmentioning
confidence: 99%
“…A novel drug delivery system utilizing oxygen-containing nanosomes has been developed to efficiently transport HDAC inhibitors to dormant HIV-infected cells. Incorporating oxygen nanosomes in this study alleviates drug toxicity and regulates the rate of drug release ( 180 ). The administration of BET inhibitors also presents side effects.…”
Section: Discussion and Expectationsmentioning
confidence: 99%
“…Studies have shown that the inhibitors of DNA methyltransferases and histone deacetylases can elevate the expression of TH1-type chemokines to promote T cell recruitment and infiltration, as well as upregulate the antigen presenting gene. 88–90 In addition, the epigenetic antitumor drugs can reprogram cancer cells to enhance the sensitivity to PD-1/PD-L1 monoclonal antibodies. 87 Significantly, the combination of epigenetic antitumor drugs with immune checkpoint inhibitors can improve the effect of immunotherapy.…”
Section: Conclusion and Prospectmentioning
confidence: 99%
“…In general, sustained reactivation of HIV-1 in the presence of optimal antiretroviral therapy and sufficient immune response will prevent new HIV-1 infection and eliminate HIV-1 from infected patients, albeit slowly . The “shock and kill” strategy aims to reactivate previral replication and transcription from the latent state using latency-reversing agents (LRAs), followed by the elimination of reactivated virus by cART and virus-producing cells by host immune clearance and HIV-1-specific cytolytic T lymphocytes (CTLs). Despite extensive and in-depth research over the years on the “shock and kill” strategy for eliminating HIV-1 reservoirs, approved compounds as LRAs cannot meet this strategy. Over 160 small-molecule compounds have been developed as LRA candidates, but none have yet demonstrated effectiveness in achieving a promising functional cure .…”
mentioning
confidence: 99%